The Strategies of Catholic Religious Teachers in Enhancing the Learning Interest of Fifth Grade Students in Elementary School - Sihotang, Din Oloan; Sinulingga, Aldi Alfrianza; Br. Tarigan, Riris Surbina (Universitas Muhammadiyah Mataram, 2023)
understanding, increasing engagement, fostering creativity and problem-solving skills, addressing student diversity, and improving knowledge retention and transfer. The use of good strategies creates a positive and meaningful learning experience for students. Hence, this research aims to explore how Catholic religious teachers in SD N 040515 Tigajumpa enhance the learning interest of fifth-grade students. The research methodology employed is qualitative. The study took place at SD N 040515 Tigajumpa, involving 15 students selected through snowball sampling. Observations and interviews were conducted during the teaching and learning process. The findings indicate that the fifth-grade students at SD N 040515 Tigajumpa display a positive learning interest in Catholic religious education. They actively engage with the teacher by asking questions and paying close attention. The teacher utilizes a Lesson Plan and addresses the variations in students' characteristics. Additionally, the teacher involves proficient students to assist their peers who may struggle. Social interaction is fostered through group discussions in the classroom. The teacher also demonstrates thorough instructional preparation. Overall, the students are physically and mentally prepared to participate in the learning process